Detection and successful endovascular treatment for a de novo intracranial pseudoaneurysm in early phase after traumatic brain injury - Sosho Kajiwara; Shuichi Tanoue; Masaru Hirohata; Yasuharu Takeuchi; Yu Hasegawa; Kimihiko Orito; Toshi Abe; Motohiro Morioka (Brain Hemorrhages, 2023)
Traumatic intracranial pseudoaneurysm (TIP) after head trauma is rare, but it frequently ruptures in early phase. Although early detection and prompt treatment is important, the details are still unknown. Here, we report a case who was diagnosed with TIP in early phase after trauma and underwent endovascular treatment with parent artery occlusion (PAO), resulted in a good outcome.A 17-year-old boy hospitalized for severe head trauma. Computed tomography (CT) revealed an acute epidural hematoma (AEDH) in the right middle fossa along with the fracture from the right lateral optic canal to the right superior orbital fissure, and CT angiography showed no obvious aneurysm at that time. CT angiography on 5 days showed an irregular shaped aneurysm at a C2-C3 posterior wall in the right internal carotid artery (ICA). As balloon occlusion test revealed complete ischemic tolerance, endovascular PAO was performed without any bypass. Postoperative imaging showed no hypoperfusion area.Prompt diagnosis for TIP is important and the patients with skull fracture around ICA area are considered to provide cerebral angiography in early phase. In addition, TIP in early phase has a risk of rupture, suitable treatment strategy using BOT is important for the favorable outcome in those patients.